Microbial Risk Assessment (MRA) As a Method of Assessment for Drinking Water Refll in Pattinggaloang District of Makassar City - Alfina Baharuddin1, Muhammad Ichsan2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Refill drinking water is one of the answers to meeting the needs of Indonesian drinking water that is cheap and practical. This is the reason why people choose AMIU to be consumed. The purpose of this study is to determine the risk of microbial drinking water in the community consumed in the working area of Pattingaloang Public Health Center in Makassar in 2019 This type of research is descriptive with Microbial Risk Assessment (MRA) assessment on refill drinking water. The sampling technique was done by a total of 6 depot drinking water refill sampling. Data processing is done by the SPPS method, the data presentation is carried out using tables accompanied by narration. Laboratory results carried out on 6 samples of refill drinking water obtained were as many as 6 samples which were stated to be Positive (+) containing bacteria. Coli Based on a Quantitative Risk Assessment, it was concluded that from 6 DAMIU samples had a high risk concentration, for the estimated number of bacteriaE. Coli in Refill Drinking Water in the surrounding area of the Pattingaloang Health Center in Makassar City. It is recommended for consumers to refill drinking water in cooking first, because pollution / contamination can occur starting from the process of taking raw water, processing and packaging / filling in gallons.